Less Expression of Prohibitin Is Associated with Increased Paired Box 2 (PAX2) in Renal Interstitial Fibrosis Rats - Tian-Biao Zhou (International Journal of Molecular Sciences, 2012)
Prohibitin (PHB) and paired box 2 (PAX2) are associated with the development of renal interstitial fibrosis (RIF). This study was performed to investigate whether or not the PHB could regulate the PAX2 gene expression in unilateral ureteral obstruction (UUO) in rats. Eighty Wistar male rats were randomly divided into two groups: sham operation group (SHO) and model group subjected to unilateral ureteral obstruction (GU), n = 40, respectively. The model was established by left ureteral ligation. Renal tissues were collected at 14-day and 28-day after surgery. RIF index, protein expression of PHB, PAX2, transforming growth factor-βl (TGF-β1), α-smooth muscle actin (α-SMA), collagen-IV (Col-IV), fibronectin (FN) or cleaved Caspase-3, and cell apoptosis index in renal interstitium, and mRNA expressions of PHB, PAX2 and TGF-β1 in renal tissue were detected. When compared with those in SHO group, expression of PHB (mRNA and protein) was significantly reduced, and expressions of PAX2 and TGF-β1 (protein and mRNA) were markedly increased in the GU group (each p < 0.01). Protein expressions of α-SMA, Col-IV, FN and cleaved Caspase-3, and RIF index or cell apoptosis index in the GU group were markedly increased when compared with those in the SHO group (each p < 0.01). The protein expression of PHB was negatively correlated with protein expression of PAX2, TGF-β1, α-SMA, Col-IV, FN or cleaved Caspase-3, and RIF index or cell apoptosis index (all p < 0.01). In conclusion, less expression of PHB is associated with increased PAX2 gene expression and RIF index in UUO rats, suggesting that increasing the PHB expression is a potential therapeutic target for prevention of RIF.